Microneedle-mediated drug delivery for cutaneous diseases - Chen, Jian; Ren, Hui; Zhou, Pan; Zheng, Shuai; Du, Bin; Liu, Xiaowen; Xiao, Fei (Frontiers in Bioengineering and Biotechnology, 2022)
Microneedles have garnered significant interest as transdermal drug delivery route owing to the advantages of nonselective loading capacity, minimal invasiveness, simple operation, and good biocompatibility. A number of therapeutics can be loaded into microneedles, including hydrophilic and hydrophobic small molecular drugs, and macromolecular drugs (proteins, mRNA, peptides, vaccines) for treatment of miscellaneous diseases. Microneedles feature with special benefits for cutaneous diseases owing to the direct transdermal delivery of therapeutics to the skin. This review mainly introduces microneedles fabricated with different technologies and transdermal delivery of various therapeutics for cutaneous diseases, such as psoriasis, atopic dermatitis, skin and soft tissue infection, superficial tumors, axillary hyperhidrosis, and plantar warts.